NAVOIY LIRIKASIDA MAY MAVZUSI - Nasimova Farog‘at Abduvali qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The article provides information about may and its poetic function in poetry, which has become traditional the mein Eastern literature. Alisher Navoi, the beloved poet of the Turkic peoples, the founder of the old and new Uzbek literary language, is involved in the analysis of such images as boda, may, chagir, kadakh, jam. Research is specially conducted on Alisher Navoi's gazals, rubais and tarjibands. May used in poet‟s poems means tasavvufiy, Navoi tried to express divine love through may and lover‟s soul through kadakh. The poet who approved vigilance in love not unconscious , advocated exact limits even in drinking may. . Since , rindona's poems are main part of Alisher Navoi's lyrics, they proves that Hazrat was a mystical poet.